Identification and Characterization of c-di-GMP Metabolic Enzymes of Leptospira interrogans and c-di-GMP Fluctuations After Thermal Shift and Infection - Xiao, Guohui; Kong, Liangliang; Che, Rongbo; Yi, Yusi; Zhang, Qinchao; Yan, Jie; Lin, Xu'ai (Frontiers in Microbiology, 2018)
Leptospirosis is a widespread zoonotic disease caused by pathogenic Leptospira species. The most common species, Leptospira interrogans, can transfer from contaminated soil or water to the human body. It is able to survive these changing environments through sensing and responding to the changes of environmental cues. Cyclic di-GMP (c-di-GMP) is a special secondary messenger in bacteria, which can respond to the environment and regulate diverse bacterial behaviors. The c-di-GMP levels in bacterial cells are regulated by diguanylatecyclases (DGC) and phosphodiesterases (PDE), which are responsible for synthesizing or hydrolyzing c-di-GMP, respectively. In this study, distribution and phylogenetics of c-di-GMP metabolic genes among 15 leptospiral species were systematically analyzed. Bioinformatics analysis revealed that leptospiral species contain a multitude of c-di-GMP metabolic genes. C-di-GMP metabolic genes in L. interrogans strain Lai 56601 were further analyzed and the results showed that these genes have very diverse expression patterns. Most of the putative DGCs and PDEs possess enzymatic activities, as determined by riboswitch-based dual-fluorescence reporters in vivo or HPLC in vitro. Furtherer analysis of subdomains from GGDEF-containing proteins revealed that the ability to synthesize c-di-GMP was lost when the GAF domain from LA1483 and PAS domain from LA2932 were deleted, while deletion of the REC domain from LA2528 did not affect its ability to synthesize c-di-GMP. Furthermore, high temperatures generally resulted in low c-di-GMP concentrations in L. interrogans and most of the c-di-GMP metabolic genes exhibited differential temperature regulation. Also, infection of murine J774A.1 cells resulted in reduced c-di-GMP levels, while no significant change of c-di-GMP metabolic genes on transcriptional levels were observed during the infection of J774A.1 cells. Taken together, these results provide a basic platform for future studies of c-di-GMP signaling pathways in Leptospira.